Cross-linked polymer as well as preparation method and application thereof
By introducing specific structural units and crosslinking agents into the crosslinking polymers and optimizing the crosslinking system, the problem of the existing high-temperature crosslinking polymers deteriorated under high temperature and high salt conditions is solved, and higher thermal stability is achieved and salt resistance, suitable for deep drilling fluid.
Patent Information
- Application Number
- CN202310771114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-28
Smart Images

Figure CN119219840A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a high temperature resistant cross-linked polymer for drilling fluid and a preparation method and application thereof. Background Art
[0002] With the increase of world energy demand and the development of drilling technology, deep and ultra-deep oil and gas have become important alternative energy sources in the world. 60% of the world's new oil and gas reserves come from deep ground, and my country still has a large amount of deep ground oil and gas to be explored and developed. Therefore, it is inevitable to search for oil and gas deep in the formation. The drilling depth in my country has reached 9,000 meters, the bottom temperature of the well is 180-260℃, and there are large sections of salt-gypsum layers in most areas, which puts higher requirements on the performance of drilling fluid treatment agents.
[0003] The solid-free (low) drilling fluid system has a good ability to carry and suspend cuttings due to its low solid content. It can also play a good lubrication and drag reduction role. It has been widely used in oilfield drilling operations. During the drilling process, in order to maintain the rheological properties of the drilling fluid system, it is usually necessary to add cross-linked polymers to increase the viscosity of the drilling fluid system. Cross-linked polymers are a type of treatment agent used in large quantities in drilling and completion fluids. They are usually made of high molecular weight polymers and are characterized by long molecular chains and good water solubility. In addition to the viscosity-increasing effect, cross-linked polymers are often used as shale inhibitors (coating agents), filtration reducers and flow pattern improvers. Therefore, the use of cross-linked polymers is often beneficial to improving the rheological properties of drilling fluids and is also beneficial to wellbore stability.
[0004] In the prior art, CN102127401A discloses a high temperature resistant cross-linked polymer for drilling fluid and a preparation method thereof, which is prepared by mixing starch, guar gum, alkaline hydroxide, epoxide and alcohol solvent in a certain proportion, and then by stirring, drying, crushing and other processes. The temperature resistance of the product in freshwater drilling fluid can reach 150°C, and the temperature resistance in seawater drilling fluid can reach 140°C. CN101955564A discloses a method for preparing a high temperature resistant and salt resistant cross-linked polymer for drilling fluid, which is prepared by aqueous solution polymerization using 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and acrylamide as raw materials. The cross-linked polymer has good stability at a formation temperature of 150°C, still has a certain effect in a 10% saline solution, and has strong salt resistance. CN 114805680 A discloses an environmentally friendly high temperature and salt resistant cross-linked polymer for water-based drilling fluid, and a preparation method and application thereof. A water-soluble high temperature resistant polymer cross-linked polymer with a certain network structure is prepared by an inverse emulsion polymerization method. The obtained cross-linked polymer has excellent viscosity increasing performance for water-based drilling fluid in a high temperature environment of 180°C and is non-toxic and easily biodegradable.
[0005] It can be seen that the temperature resistance of domestic high temperature cross-linked polymer products is usually around 150-180°C, and when the mineralization degree of the system is high (especially Ca 2+ Concentration higher than 1.4×10 4 mg / L), the cross-linked polymer will have molecular chain curling and winding, resulting in product failure. Conventional aqueous solution polymerization methods have certain limitations. This field is in urgent need of developing a cross-linked polymer product that can still maintain good performance under high temperature and high salt conditions. Summary of the invention
[0006] At present, in the prior art, when improving the performance of cross-linked polymers, the optimization direction is still mainly focused on the selection of polymer monomer structure. However, the temperature resistance of high-temperature resistant cross-linked polymer products at this stage is only about 180°C at most, and the salt resistance is relatively poor. There is still room for further improvement in practical applications. However, this application found that by optimizing the cross-linking system, the thermal stability of the product can be enhanced while further enhancing the salt resistance.
[0007] Based on this, the specific technical solutions of the present invention are as follows:
[0008] In a first aspect, the present invention first provides a cross-linked polymer, wherein the cross-linked polymer comprises a sulfonic acid structural unit, an acrylamide structural unit, a first cross-linking unit and a second cross-linking unit;
[0009] Wherein, the first cross-linking unit is The second crosslinking unit is C1 to C 25 of a straight chain alkyl group.
[0010] The present invention finds that through the synergy of the above two cross-linking units, not only the cross-linking strength can be significantly enhanced, but also the spatial network structure of the molecule can be strengthened, thereby improving the viscosity increasing performance of the product; at the same time, the above carbon-carbon long chain structure can further enhance the thermal stability of the cross-linked polymer, and can effectively inhibit the curling of the molecular chain under high salt conditions, thereby improving the salt resistance of the product.
[0011] Preferably, the second crosslinking unit is C6 to C 10 When a straight-chain alkyl group is added, the salt resistance and temperature resistance can be further improved.
[0012] Preferably, the mass ratio of the total mass of the sulfonic acid structural unit and the acrylamide structural unit to the mass ratio of the second cross-linking unit is 5000-10000:1-5.
[0013] The present invention further finds that by controlling the amount of the second cross-linking unit, excessive cross-linking of the cross-linked polymer can be effectively avoided, thereby further improving product stability, water solubility and other properties.
[0014] Preferably, the sulfonic acid structural unit is selected from one or more of 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamidododecylsulfonic acid, 2-acryloxy-2-methylpropanesulfonic acid, acryloxybutylsulfonic acid, 2-acrylamidotetradecanesulfonic acid and N-methyldiallylpropanesulfonic acid.
[0015] Preferably, the acrylamide structural unit is selected from one or more of N-(3-dimethylaminopropyl)methacrylamide, N-(2-hydroxyethyl)-2-methyl-2-acrylamide, N-isopropylmethacrylamide, N-methylacrylamide and N-hydroxymethylacrylamide.
[0016] Preferably, the cross-linked polymer is selected from one of the following general structures:
[0017]
[0018] Wherein, n represents the number of carbon atoms, 1≤n≤25; and R is selected from H, -CH2CH2CH2N(CH3)2, -CH2CH2OH, -(CH3)2 or -CH2OH.
[0019] Preferably, the degree of polymerization of the cross-linked polymer is 50,000 to 500,000.
[0020] Preferably, based on the total weight of the cross-linked polymer, the content of the second cross-linked unit is 0.01-0.05wt%; the content of the sulfonic acid structural unit is 30-60wt%; the content of the acrylamide structural unit is 40-80wt%; and the content of the first cross-linked unit is 0.01-0.05wt%.
[0021] In a second aspect, the present invention further provides a method for preparing the cross-linked polymer, comprising: using a sulfonic acid monomer and an acrylamide monomer as raw materials, and preparing the cross-linked polymer by secondary cross-linking;
[0022] The first crosslinking agent used in the first crosslinking is 1,4-divinylbenzene; the second crosslinking agent used in the second crosslinking is one or more of dihalogenated alkanes.
[0023] The present invention finds that by using 1,4-divinylbenzene with a rigid benzene ring structure to perform preliminary crosslinking of sulfonic acid monomers and acrylamide monomers, and combining with dihalogenated hydrocarbons to perform secondary crosslinking of secondary amine groups in the polymer through an alkylation reaction, the crosslinking strength can be significantly improved while enhancing the thermal stability of the crosslinked polymer, and the curling of the molecular chain under high salt conditions can be effectively inhibited, thereby improving the salt resistance of the product.
[0024] In the present invention, the cross-linked polymer is obtained by inverse emulsion polymerization, and heat is evenly dissipated during the reaction process without explosion due to local overheating.
[0025] Preferably, the dihaloalkane is selected from 1,2-dichloroethane, 1,2-dichloropropane, 1,3-dichloropropane, 1,2-dichlorobutane, 1,3-dichlorobutane, 1,4-dichlorobutane, 1,2-dichloropentane, 1,3-dichloropentane, 1,4-dichloropentane, 1,5-dichloropentane, 1,2-dichlorohexane, 1,3-dichlorohexane, 1,4-dichlorohexane, 1,5 -dichlorohexane, 1,6-dichlorohexane, 1,2-dichloroheptane, 1,3-dichloroheptane, 1,4-dichloroheptane, 1,5-dichloroheptane, 1,6-dichloroheptane, 1,7-dichloroheptane, 1,2-dichlorooctane, 1,3-dichlorooctane, 1,4-dichlorooctane, 1,5-dichlorooctane, 1,6-dichlorooctane, 1,7-dichlorooctane, 1,8-dichlorooctane, 1,2 -dichlorononane, 1,3-dichlorononane, 1,4-dichlorononane, 1,5-dichlorononane, 1,6-dichlorononane, 1,7-dichlorononane, 1,8-dichlorononane, 1,9-dichlorononane, 1,2-dichlorodecane, 1,3-dichlorodecane, 1,4-dichlorodecane, 1,5-dichlorodecane, 1,6-dichlorodecane, 1,7-dichlorodecane, 1,8-dichlorodecane, 1,9 -dichloropentane, 1,10-dichloropentane; 1,2-diiodoethane, 1,2-diiodopropane, 1,3-diiodopropane, 1,2-diiodobutane, 1,3-diiodobutane, 1,4-diiodobutane, 1,2-diiodopentane, 1,3-diiodopentane, 1,4-diiodopentane, 1,5-diiodopentane, 1,2-diiodohexane, 1,3-diiodohexane, 1,4-diiodohexane, 1,
[0026] 5-diiodohexane, 1,6-diiodohexane, 1,2-diiodoheptane, 1,3-diiodoheptane, 1,
[0027] 4-diiodoheptane, 1,5-diiodoheptane, 1,6-diiodoheptane, 1,7-diiodoheptane, 1,
[0028] 2-Diiodooctane, 1,3-Diiodooctane, 1,4-Diiodooctane, 1,5-Diiodooctane, 1,
[0029] 6-diiodooctane, 1,7-diiodooctane, 1,8-diiodooctane, 1,2-diiodononane, 1,
[0030] 3-diiodononane, 1,4-diiodononane, 1,5-diiodononane, 1,6-diiodononane, 1,
[0031] 7-diiodononane, 1,8-diiodononane, 1,9-diiodononane, 1,2-diiododecane, 1,
[0032] 3-diiododecane, 1,4-diiododecane, 1,5-diiododecane, 1,6-diiododecane, 1,
[0033] 7-diiododecane, 1,8-diiododecane, 1,9-diiododecane, 1,10-diiododecane; 1,
[0034] 2-dibromoethane, 1,2-dibromopropane, 1,3-dibromopropane, 1,2-dibromobutane, 1,
[0035] 3-Dibromobutane, 1,4-dibromobutane, 1,2-dibromopentane, 1,3-dibromopentane, 1,
[0036] 4-dibromopentane, 1,5-dibromopentane, 1,2-dibromohexane, 1,3-dibromohexane, 1,
[0037] 4-dibromohexane, 1,5-dibromohexane, 1,6-dibromohexane, 1,2-dibromoheptane, 1,
[0038] 3-dibromoheptane, 1,4-dibromoheptane, 1,5-dibromoheptane, 1,6-dibromoheptane, 1,
[0039] 7-dibromoheptane, 1,2-dibromooctane, 1,3-dibromooctane, 1,4-dibromooctane, 1,
[0040] 5-dibromooctane, 1,6-dibromooctane, 1,7-dibromooctane, 1,8-dibromooctane, 1,
[0041] 2-Dibromononane, 1,3-Dibromononane, 1,4-Dibromononane, 1,5-Dibromononane, 1,
[0042] 6-dibromononane, 1,7-dibromononane, 1,8-dibromononane, 1,9-dibromononane, 1,
[0043] 2-Dibromodecane, 1,3-Dibromodecane, 1,4-Dibromodecane, 1,5-Dibromodecane, 1,
[0044] 6-dibromodecane, 1,7-dibromodecane, 1,8-dibromodecane, 1,9-dibromodecane, 1,
[0045] 10-dibromodecane; 1,2-difluoroethane, 1,2-difluoropropane, 1,3-difluoropropane, 1,
[0046] 2-difluorobutane, 1,3-difluorobutane, 1,4-difluorobutane, 1,2-difluoropentane, 1,
[0047] 3-difluoropentane, 1,4-difluoropentane, 1,5-difluoropentane, 1,2-difluorohexane, 1,
[0048] 3-difluorohexane, 1,4-difluorohexane, 1,5-difluorohexane, 1,6-difluorohexane, 1,
[0049] 2-difluoroheptane, 1,3-difluoroheptane, 1,4-difluoroheptane, 1,5-difluoroheptane, 1,
[0050] 6-difluoroheptane, 1,7-difluoroheptane, 1,2-difluorooctane, 1,3-difluorooctane, 1,
[0051] 4-difluorooctane, 1,5-difluorooctane, 1,6-difluorooctane, 1,7-difluorooctane, 1,
[0052] 8-difluorooctane, 1,2-difluorononane, 1,3-difluorononane, 1,4-difluorononane, 1,5-difluorononane, 1,6-difluorononane, 1,7-difluorononane, 1,8-difluorononane, 1,9-difluorononane, 1,2-difluorodecane, 1,3-difluorodecane, 1,4-difluorodecane, 1,5-difluorodecane, 1,6-difluorodecane, 1,7-difluorodecane, 1,8-difluorodecane, 1,9-difluorodecane or 1,10-difluorodecane.
[0053] More preferably, the dihaloalkane is selected from 1,6-dibromohexane, 1,7-dibromoheptane, 1,8-dibromooctane, 1,9-dibromononane or 1,10-dibromodecane.
[0054] Preferably, the sulfonic acid monomer is selected from one or more of 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamidododecylsulfonic acid, 2-acryloxy-2-methylpropanesulfonic acid, acryloxybutylsulfonic acid, 2-acrylamidotetradecanesulfonic acid and N-methyldiallylpropanesulfonic acid.
[0055] More preferably, the sulfonic acid monomer is selected from 2-acrylamide-2-methylpropanesulfonic acid or 2-acrylamide dodecylsulfonic acid.
[0056] The present invention finds that when the molecular structure contains the above-mentioned carbon-carbon long chain and sulfonic acid group, the thermal stability and water solubility of the cross-linked polymer can be further improved.
[0057] Preferably, the acrylamide monomer is a monomer having a secondary amine group; more preferably, the acrylamide monomer is selected from one or more of N-(3-dimethylaminopropyl)methacrylamide, N-(2-hydroxyethyl)-2-methyl-2-acrylamide, N-isopropylmethacrylamide, N-methylacrylamide and N-hydroxymethylacrylamide.
[0058] The present invention finds that the side chains of the acrylamide monomer molecules contain a certain amount of methyl or hydroxyl groups, which helps to increase the steric hindrance of the polymer, thereby further improving the salt resistance.
[0059] Preferably, the amount of the second cross-linking agent is 0.01-0.05 wt % of the total weight of the sulfonic acid monomer and the acrylamide monomer.
[0060] Preferably, the first cross-linking agent is used in an amount of 0.01 to 0.05 wt % of the total weight of the sulfonic acid monomer and the acrylamide monomer.
[0061] Preferably, the mass ratio of the first cross-linking agent to the second cross-linking agent is (0.7-1.5):1.
[0062] Preferably, the mass ratio of the sulfonic acid monomer to the acrylamide monomer is 1-5:1-5.
[0063] Preferably, the method for preparing the cross-linked polymer comprises the following steps:
[0064] S1: mixing sulfonic acid monomer, acrylamide monomer and water to obtain an aqueous phase;
[0065] S2: adding alkaline substances to the aqueous phase to adjust the pH of the aqueous phase to 7-8;
[0066] S3: mixing the white oil, the emulsifier and the first cross-linking agent to obtain an oil phase;
[0067] S4: mixing the water phase and the oil phase to obtain an emulsion;
[0068] S5: mixing the emulsion and the initiator under a nitrogen atmosphere and a temperature of 30 to 80° C. to react to obtain a reaction solution;
[0069] S6: mixing the reaction solution with a second cross-linking agent to react, and the obtained product is the cross-linked polymer.
[0070] Preferably, in S1, the mass ratio of the total mass of the sulfonic acid monomer and the acrylamide monomer to the water is (0.5-1.5):1.
[0071] Preferably, in S2, the alkaline substance can be an inorganic base and / or an alkaline inorganic salt, and the metal element in the inorganic base and / or the alkaline inorganic salt is selected from one or more of monovalent, divalent, trivalent, and tetravalent metals, and can be further specifically selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, magnesium hydroxide, magnesium carbonate, calcium carbonate, calcium hydroxide, iron hydroxide, copper hydroxide, titanium hydroxide, zirconium hydroxide, etc., and preferably one or more of sodium hydroxide and potassium hydroxide.
[0072] Preferably, in S3, the white oil is industrial white oil; preferably, the industrial asphalt is selected from one or more of No. 3 industrial white oil, No. 5 industrial white oil, No. 7 industrial white oil, No. 10 industrial white oil, No. 15 industrial white oil, No. 20 industrial white oil, No. 22 industrial white oil, No. 26 industrial white oil, No. 32 industrial white oil, No. 48 industrial white oil and No. 64 industrial white oil.
[0073] More preferably, the mass ratio of the white oil to the water in S1 is (0.8-1.5):1.
[0074] Preferably, in S3, the emulsifier is selected from one or more of op10, span80 and tween60.
[0075] More preferably, the emulsifier is a composite emulsifier of span80 and op10 in a mass ratio of (4-10):1; or,
[0076] The emulsifier is a composite emulsifier of span80 and tween60 in a mass ratio of (4-10):1.
[0077] More preferably, the amount of the emulsifier is 2-10% of the total mass of the sulfonic acid monomer and the acrylamide monomer.
[0078] In specific implementation, for the above-mentioned mixing operation, those skilled in the art can make the mixing uniform based on the existing technology and the conventional technical capabilities in the field.
[0079] Preferably, in S4, the stirring rate is controlled at 150-400 rpm when the oil phase and the water phase are mixed.
[0080] Preferably, in S5, the initiator is selected from persulfate and / or azo compound; the persulfate is selected from one or more of potassium persulfate, sodium persulfate and ammonium persulfate; the azo compound is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride and azobisisobutylimidazoline hydrochloride.
[0081] More preferably, the amount of the initiator is 0.5-5‰ of the total mass of the sulfonic acid monomer and the acrylamide monomer.
[0082] Preferably, in S5, the reaction temperature is 40-70°C.
[0083] Preferably, in S5, the reaction time is 1 to 6 hours.
[0084] Preferably, in S6, the reaction time is 0.5 to 2 hours.
[0085] In a third aspect, the present invention provides use of the cross-linked polymer in drilling fluid or completion fluid.
[0086] In the present invention, the cross-linked polymer can be used for oil field polymers such as viscosity enhancement, cutting enhancement, drilling and completion, as well as water treatment, papermaking industry, fiber industry, coating industry, water absorbing materials, printing and dyeing auxiliaries, biomedicine and other fields.
[0087] Preferably, the cross-linked polymer is used as a viscosity increasing agent.
[0088] Preferably, the amount of the cross-linked polymer used in the drilling fluid when used as a viscosity enhancer is 3 to 30 g / L.
[0089] Preferably, the amount of the cross-linked polymer used in the completion fluid when used as a viscosity enhancer is 0.3 to 30 g / L.
[0090] In a fourth aspect, the present invention provides a drilling fluid comprising the above-mentioned cross-linked polymer.
[0091] In a fifth aspect, the present invention provides a completion fluid comprising the above-mentioned cross-linked polymer.
[0092] Based on the above technical solution, the beneficial effects of the present invention are:
[0093] The present invention can significantly improve the viscosity retention rate of the cross-linked polymer at high temperature by optimizing the cross-linking system, and can enhance the salt resistance (resistance to NaCl saturation, resistance to CaCl2 saturation), while also having good shearing power. DETAILED DESCRIPTION
[0094] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0095] Unless otherwise specified, all raw materials used in the examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0096] Example 1
[0097] This embodiment provides a cross-linked polymer, the structural formula of which is as follows:
[0098]
[0099] This embodiment further provides a method for preparing the above cross-linked polymer, comprising the following steps:
[0100] Add 20g of 2-acrylamido-2-methylpropanesulfonic acid, 20g of N-(2-hydroxyethyl)-2-methyl-2-acrylamide, and 70g of water to a flask and stir until the solution is uniform to obtain an aqueous phase. Add 3.9g of NaOH to the aqueous phase and adjust the pH to 7. Weigh 65g of 7 # Add white oil to a beaker, add 0.66g Span80, 0.14g Tween60, 0.004g 1,4-divinylbenzene, stir evenly to obtain an oil phase. Then add the oil phase to a flask, mix with the aqueous phase, and stir thoroughly for 30 minutes to obtain an emulsion. Dissolve 0.04g potassium persulfate completely in 10g water, and under a nitrogen atmosphere and 40°C, mix the emulsion with the potassium persulfate aqueous solution to react to obtain a reaction solution. After the reaction is carried out for 2 hours, add 0.004g 1,6-dibromohexane to the reaction solution, continue the reaction for 2 hours, and then stop the reaction. The resulting product is a cross-linked polymer.
[0101] Example 2
[0102] This embodiment provides a cross-linked polymer, the structural formula of which is as follows:
[0103]
[0104] This embodiment further provides a method for preparing the above cross-linked polymer, comprising the following steps:
[0105] Add 10g 2-acrylamidododecylsulfonic acid, 20g methacrylamide, and 40g water into a flask and stir until the solution is uniform to obtain an aqueous phase. Add 1.76g KOH to the aqueous phase and adjust the pH to 7. Weigh 50g 7 # Add white oil to a beaker, add 1.3g Span80, 0.2g Tween60, 0.009g 1,4-divinylbenzene, stir evenly to obtain an oil phase. Then add the oil phase to a flask, mix with the water phase, and stir thoroughly for 30 minutes to obtain an emulsion. Dissolve 0.06g ammonium persulfate completely in 10g water, and under a nitrogen atmosphere and 50°C, mix the emulsion with an aqueous solution of ammonium persulfate to react to obtain a reaction solution. After the reaction is carried out for 3 hours, add 0.006g 1,6-dibromoheptane to the reaction solution, continue the reaction for 0.5 hours, and then stop the reaction. The resulting product is a cross-linked polymer.
[0106] Example 3
[0107] This embodiment provides a cross-linked polymer, the structural formula of which is as follows:
[0108]
[0109] This embodiment further provides a method for preparing the cross-linked polymer, comprising the following steps:
[0110] Add 25g of 2-acrylamidododecylsulfonic acid, 5g of methacrylamide, and 20g of water to a flask and stir until the solution is uniform to obtain an aqueous phase. Add 4.4g of KOH to the aqueous phase and adjust the pH to 7. Weigh 30g of 7 # Add 1.35g Span80, 0.15g Tween60 and 0.015g 1,4-divinylbenzene to the white oil in a beaker, stir evenly to obtain an oil phase. Then add the oil phase to a flask, mix with the water phase, and stir thoroughly for 30 minutes to obtain an emulsion. Dissolve 0.06g of azobisisobutylamidine hydrochloride completely in 10g of water, and mix the emulsion with an aqueous solution of azobisisobutylamidine hydrochloride under a nitrogen atmosphere at 60°C to react to obtain a reaction solution. After the reaction is carried out for 6 hours, add 0.015g 1,6-dibromooctane to the reaction solution, continue the reaction for 2 hours, and then stop the reaction. The resulting product is a cross-linked polymer.
[0111] Example 4
[0112] This embodiment provides a cross-linked polymer, whose structural formula is the same as that of embodiment 1, and whose preparation method comprises the following steps:
[0113] Add 10g 2-acrylamido-2-methylpropanesulfonic acid, 30g N-(2-hydroxyethyl)-2-methyl-2-acrylamide, and 90g water to a flask and stir until the solution is uniform to obtain an aqueous phase. Add 1.95g NaOH to the aqueous phase and adjust the pH to 7. Weigh 80g 7 # Add white oil to a beaker, add 0.66g Span80, 0.14g Tween60, 0.003g 1,4-divinylbenzene, stir evenly to obtain an oil phase. Then add the oil phase to a flask, mix with the aqueous phase, and stir thoroughly for 30 minutes to obtain an emulsion. Dissolve 0.04g potassium persulfate completely in 10g water, and under a nitrogen atmosphere and 50°C, mix the emulsion with an aqueous solution of potassium persulfate to react to obtain a reaction solution. After the reaction is carried out for 1 hour, add 0.004g 1,6-dibromohexane to the reaction solution, continue the reaction for 2 hours, and then stop the reaction. The resulting product is a cross-linked polymer.
[0114] Example 5
[0115] This embodiment provides a cross-linked polymer, whose structural formula is the same as that of the preparation method embodiment 1, except that the mass ratio of the first cross-linking agent to the second cross-linking agent is 2:1.
[0116] Comparative Example 1
[0117] This comparative example provides a cross-linked polymer, whose structural formula and preparation method are the same as those of Example 1, except that 1,6-dibromohexane is replaced by an equal amount of N,N-methylenebisacrylamide.
[0118] Comparative Example 2
[0119] This comparative example provides a cross-linked polymer, whose structural formula and preparation method are the same as those of Example 1, except that the second cross-linking agent is replaced by an equal amount of the first cross-linking agent.
[0120] In order to further illustrate the technical effects of the present invention, the present invention also provides effect tests of the above embodiments and comparative examples in actual applications.
[0121] Test example
[0122] 1. Adhesion and temperature resistance test
[0123] Preparation of polymer solution: Add 3.5 g of the cross-linked polymer prepared in the example and the comparative example into 350 mL of deionized water, and stir at 8000 r / min for 20 min to obtain a polymer solution sample.
[0124] Performance test: The apparent viscosity of the polymer solution was measured at room temperature using a six-speed viscometer according to the method specified in the national standard GB / T 16783.1-2006. After the measurement, the polymer solution was transferred to a high-temperature roller furnace and aged at 180°C for 16 hours. After the aging was completed, the solution temperature was cooled to room temperature and stirred at 8000r / min for 20 minutes to measure the apparent viscosity of the aged polymer solution. The apparent viscosity data before and after aging are listed in Table 1.
[0125] Table 1 Test results of polymer viscosity enhancement and temperature resistance
[0126]
[0127] 2. Salt resistance test
[0128] Preparation of polymer saturated salt solution: At room temperature and under stirring conditions, continuously add NaCl to 350mL of deionized water until the solution can no longer dissolve NaCl, and a saturated NaCl solution is obtained. Add 3.5mL of polymer sample to 350mL of saturated NaCl solution, and stir at 8000r / min for 20min to obtain a polymer saturated NaCl solution. The preparation method of polymer saturated CaCl2 solution is the same as that of polymer saturated NaCl solution.
[0129] Performance test: The apparent viscosity of the polymer solution was measured at room temperature using a six-speed viscometer according to the method specified in the national standard GB / T 16783.1-2006. After the measurement, the polymer solution was transferred to a high-temperature roller furnace and aged at 180°C for 16 hours. After the aging, the solution temperature was cooled to room temperature and stirred at 8000r / min for 20 minutes to measure the apparent viscosity of the aged polymer solution. The apparent viscosity data of the polymer saturated NaCl solution and the polymer saturated CaCl2 solution before and after aging are listed in Table 2 and Table 3, respectively.
[0130] Table 2 Test results of polymer NaCl resistance
[0131]
[0132] Table 3 Test results of polymer anti-CaCl2 performance
[0133]
[0134]
[0135] From the data in Tables 1 to 3, it can be seen that the cross-linked polymer prepared by the present invention has excellent viscosity-increasing, salt-resistant and shear-reducing properties, and still has a high viscosity retention rate after aging at a high temperature of 180°C for 16 hours. The polymer can maintain good viscosity-increasing properties in a saturated salt solution, and the apparent viscosity of the solution after aging is much higher than the data in the comparative example. In addition, the shear force of the polymer aqueous solution always remains at a high level before and after aging, indicating that the cross-linked polymer prepared by the present invention has good rock-carrying performance.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cross-linked polymer, characterized in that The cross-linked polymer comprises a sulfonic acid structural unit, an acrylamide structural unit, a first cross-linking unit and a second cross-linking unit; Wherein, the first cross-linking unit is The second crosslinking unit is C1 to C 25 of a straight chain alkyl group.
2. The cross-linked polymer according to claim 1, characterized in that The second crosslinking unit is C6~C 10 of a straight chain alkyl group.
3. The cross-linked polymer according to claim 1 or 2, characterized in that The mass ratio of the total mass of the sulfonic acid structural unit and the acrylamide structural unit to the mass ratio of the second cross-linking unit is 5000-10000:1-5.
4. The cross-linked polymer according to any one of claims 1 to 3, characterized in that The sulfonic acid structural unit includes one or more of 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamidododecylsulfonic acid, 2-acryloxy-2-methylpropanesulfonic acid, acryloxybutylsulfonic acid, 2-acrylamidotetradecanesulfonic acid and N-methyldiallylpropanesulfonic acid; and / or The acrylamide structural unit includes one or more of N-(3-dimethylaminopropyl)methacrylamide, N-(2-hydroxyethyl)-2-methyl-2-acrylamide, N-isopropylmethacrylamide, N-methylacrylamide and N-hydroxymethylacrylamide.
5. The cross-linked polymer according to claim 1, characterized in that The cross-linked polymer is selected from one of the following structures: Wherein, n represents the number of carbon atoms, 1≤n≤25; the R is selected from -H, -CH2CH2CH2N(CH3)2, -CH2CH2OH, -(CH3)2 or -CH2OH; preferably, the degree of polymerization of the cross-linked polymer is 50,000 to 500,000.
6. The cross-linked polymer according to any one of claims 1 to 5, characterized in that Based on the total weight of the cross-linked polymer, the content of the second cross-linked unit is 0.01-0.05wt%; the content of the sulfonic acid structural unit is 30-60wt%; the content of the acrylamide structural unit is 40-80wt%; and the content of the first cross-linked unit is 0.01-0.05wt%.
7. The method for preparing a cross-linked polymer according to any one of claims 1 to 6, characterized in that: The cross-linked polymer is prepared by secondary cross-linking using sulfonic acid monomers and acrylamide monomers as raw materials; The first crosslinking agent used in the primary crosslinking is 1,4-divinylbenzene; and the second crosslinking agent used in the secondary crosslinking is one or more of dihalogenated alkanes.
8. The method for preparing a cross-linked polymer according to claim 7, characterized in that: The second cross-linking agent is selected from 1,6-dibromohexane, 1,7-dibromoheptane, 1,8-dibromooctane, 1,9-dibromononane or 1,10-dibromodecane.
9. The method for preparing a cross-linked polymer according to claim 7 or 8, characterized in that: The sulfonic acid monomer is selected from one or more of 2-acrylamide-2-methylpropanesulfonic acid and 2-acrylamide dodecylsulfonic acid; and / or The acrylamide monomer is a monomer having a secondary amine group; preferably, the acrylamide monomer is selected from one or more of N-(3-dimethylaminopropyl)methacrylamide, N-(2-hydroxyethyl)-2-methyl-2-acrylamide, N-isopropylmethacrylamide, N-methylacrylamide and N-hydroxymethylacrylamide.
10. The method for preparing a cross-linked polymer according to any one of claims 7 to 9, characterized in that: The mass ratio of the first cross-linking agent to the second cross-linking agent is (0.7-1.5):
1.
11. The method for preparing a cross-linked polymer according to any one of claims 7 to 10, characterized in that: The mass ratio of the sulfonic acid monomer to the acrylamide monomer is 1-5:1-5.
12. The method for preparing a cross-linked polymer according to any one of claims 7 to 11, characterized in that: include: S1: mixing sulfonic acid monomer, acrylamide monomer and water to obtain an aqueous phase; S2: adding alkaline substances to the aqueous phase to adjust the pH of the aqueous phase to 7-8; S3: mixing the white oil, the emulsifier and the first cross-linking agent to obtain an oil phase; S4: mixing the water phase and the oil phase to obtain an emulsion; S5: mixing the emulsion and the initiator under a nitrogen atmosphere and a temperature of 30 to 80° C. to react to obtain a reaction solution; S6: mixing the reaction solution with a second cross-linking agent to react, and the obtained product is the cross-linked polymer.
13. The method for preparing a cross-linked polymer according to claim 12, characterized in that: In S1, the mass ratio of the total mass of the sulfonic acid monomer and the acrylamide monomer to water is (0.5-1.5):
1.
14. The method for preparing a cross-linked polymer according to claim 12 or 13, characterized in that: In S3, the white oil is industrial white oil; Preferably, the industrial white oil is selected from one or more of No. 3 industrial white oil, No. 5 industrial white oil, No. 7 industrial white oil, No. 10 industrial white oil, No. 15 industrial white oil, No. 20 industrial white oil, No. 22 industrial white oil, No. 26 industrial white oil, No. 32 industrial white oil, No. 48 industrial white oil and No. 64 industrial white oil; Preferably, the mass ratio of the white oil to the water in S1 is (0.8-1.5):
1.
15. The method for preparing a cross-linked polymer according to any one of claims 12 to 14, characterized in that: In S3, the emulsifier is selected from one or more of op10, span80 and tween60; Preferably, the emulsifier is a composite emulsifier of span80 and op10 in a mass ratio of (4-10):1; or, the emulsifier is a composite emulsifier of span80 and tween60 in a mass ratio of (4-10):1; More preferably, the amount of the emulsifier is 2-10 wt % of the total weight of the sulfonic acid monomer and the acrylamide monomer.
16. The method for preparing a cross-linked polymer according to any one of claims 12 to 15, characterized in that: In S5, the initiator is selected from persulfate and / or azo compound; the persulfate is selected from one or more of potassium persulfate, sodium persulfate and ammonium persulfate; the azo compound is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride and azobisisobutylimidazoline hydrochloride; Preferably, the amount of the initiator is 0.5 to 5 wt‰ of the total mass of the sulfonic acid monomer and the acrylamide monomer.
17. Use of the cross-linked polymer according to any one of claims 1 to 6 or the cross-linked polymer prepared by the preparation method according to any one of claims 7 to 16 in drilling fluid or completion fluid; preferably, the cross-linked polymer is used as a viscosity enhancer.
18. The use according to claim 17, characterized in that When the cross-linked polymer is used as a viscosity enhancer, the amount of the cross-linked polymer used in the drilling fluid or completion fluid is 3 to 30 g / L.
19. A drilling fluid, characterized in that: It contains the cross-linked polymer according to any one of claims 1 to 6 or the cross-linked polymer prepared by the preparation method according to any one of claims 7 to 16.
20. A completion fluid, characterized in that: It contains the cross-linked polymer according to any one of claims 1 to 6 or the cross-linked polymer prepared by the preparation method according to any one of claims 7 to 16.
Citation Information
Patent Citations
Temperature-resistant microcross-linked tackifier and high-temperature-resistant solid-free water-based drilling fluid
CN104650827A
Micro-crosslinked amphoteric polyacrylamide and preparation method thereof
CN107880215A
High-temperature-resistant salt-resistant cross-linked polymer filtrate reducer as well as preparation method and application thereof
CN114181682A
Crosslinked polymer compositions with two crosslinkers for use in subterranean formation operations
US20180002470A1